2021
DOI: 10.3389/fcimb.2020.557515
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition Changes in Constipated Women of Reproductive Age

Abstract: BackgroundChronic constipation is one of the most prevalent functional gastrointestinal disorders, yet its etiology is multifactorial, and the pathophysiological mechanism is still unclear. Previous studies have shown that the gut microbiota of constipated patients differs from healthy controls; however, many discrepancies exist in the findings, and no clear link has been confirmed between chronic constipation and changes in the gut microbiota. Growing evidence indicates that age, gender, and hormone levels ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Together, these results showed that positive alterations of microbial community richness and diversity were exerted by FMT, suggesting that this might be a potential therapeutic mechanism [25]. The gut microbiota in patients with constipation are different from the healthy controls, manifesting as the increasing abundance of Bacteroides and the decreasing abundance of Proteobacteria [26]. Khalif et al found that Bifidobacteria and Lactobacillus significantly decreased in the 57 Fig.…”
Section: L-arginine and L-threonine Are Involved In The Protein Digestion And Absorption Pathwaymentioning
confidence: 87%
“…Together, these results showed that positive alterations of microbial community richness and diversity were exerted by FMT, suggesting that this might be a potential therapeutic mechanism [25]. The gut microbiota in patients with constipation are different from the healthy controls, manifesting as the increasing abundance of Bacteroides and the decreasing abundance of Proteobacteria [26]. Khalif et al found that Bifidobacteria and Lactobacillus significantly decreased in the 57 Fig.…”
Section: L-arginine and L-threonine Are Involved In The Protein Digestion And Absorption Pathwaymentioning
confidence: 87%
“…Acute appendicitis is characterized by elevated levels of Fusobacterium ( Swidsinski et al, 2011 ; Guinane et al, 2013 ; Jackson et al, 2014 ; Zhong et al, 2014 ; Rogers et al, 2016 ), Parvimonas ( Guinane et al, 2013 ; Jackson et al, 2014 ; Zhong et al, 2014 ; Rogers et al, 2016 ), Campylobacter jejuni ( Campbell et al, 2006 ; Oh et al, 2020b ), and Gemella ( Guinane et al, 2013 ; Zhong et al, 2014 ), and reduced levels of Bacteroides ( Swidsinski et al, 2011 ; Samuelsson et al, 2013 ; Zhong et al, 2014 ; Rogers et al, 2016 ), Ruminococcus ( Samuelsson et al, 2013 ; Munakata et al, 2021 ), and Faecalibacterium ( prausnitzii ) ( Swidsinski et al, 2011 ; Samuelsson et al, 2013 ). The gut microbiome signature of chronic constipation consists of large proportions of Clostridium ( Zoppi et al, 1998 ; Zhu et al, 2014 ) and Parabacteroides ( de Meij et al, 2016 ; Li et al, 2020b ), and depressed amounts of Lactobacillus ( Khalif et al, 2005 ; Moraes et al, 2016 ; Jomehzadeh et al, 2020 ) and Roseburia ( Mancabelli et al, 2017 ; Li et al, 2020b ). Stool analysis of patients with inflammatory bowel disease (IBD) frequently demonstrates overrepresentation of Veillonella ( Gevers et al, 2014 ; Mottawea et al, 2016 ; Santoru et al, 2017 ; Schirmer et al, 2018 ) and Escherichia coli ( Schwiertz et al, 2010 ; Sha et al, 2013 ; Gevers et al, 2014 ; Santoru et al, 2017 ), and underrepresentation of Faecalibacterium ( prausnitzii ) ( Schwiertz et al, 2010 ; Joossens et al, 2011 ; Morgan et al, 2012 ; Kumari et al, 2013 ; Gevers et al, 2014 ; Machiels et al, 2014 ; Schirmer et al, 2018 ), and Roseburia ( Morgan et al, 2012 ...…”
Section: Gut Microbiome Changes In Diseases Affecting the Human Diges...mentioning
confidence: 99%
“…Recent studies using 16S rRNA-based microbiota profiling have demonstrated dysbiosis of gut microbiota in constipation ( Ohkusa et al., 2019 ). Although the findings are inconsistent and currently no consensus exists, studies in constipation have found significant inter-individual differences between healthy individual and patients ( Zhu et al., 2014 ; Mancabelli et al., 2017 ; Li et al., 2020 ). Interestingly, results of alpha-diversity analysis from these studies suggested similar community richness and diversity between the two groups ( Li et al., 2020 ), which were consistent with our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Although the findings are inconsistent and currently no consensus exists, studies in constipation have found significant inter-individual differences between healthy individual and patients ( Zhu et al., 2014 ; Mancabelli et al., 2017 ; Li et al., 2020 ). Interestingly, results of alpha-diversity analysis from these studies suggested similar community richness and diversity between the two groups ( Li et al., 2020 ), which were consistent with our findings. Evidence from a mouse study showed the causal relationship between dysbiosis and chronic constipation.…”
Section: Discussionmentioning
confidence: 98%